Effect of swimming pools on antibiotic use and clinic attendance for infections in two Aboriginal communities in Western Australia - Silva, D.; Lehmann, Deborah; Tennant, M.; Jacoby, P; Wright, H.; Stanley, F (Australian Medical Association, 2008)
Objective:To determine whether installation of swimming pools in remote Aboriginal communities reduces infection-related outpatient attendances and prescription of antibiotics. Design and setting: Swimming pools were opened in Jigalong and Mugarinya, Western Australia, in September 2000. We examined local clinic records to document illnesses occurring in children and adolescents under 17 years of age between 1998 and 2005. In Jigalong, we examined records of those enrolled in an ongoing study evaluating the effect of swimming pools on health. In Mugarinya, we examined clinic records of those residing there permanently.Main outcome measures:Clinic attendance rates for skin, middle-ear and respiratory tract infections and trauma, and prescription rates for antibiotics were analysed by using a community-based selection method in Jigalong, and a clinic-based selection method in both communities for comparison of the two communities and the two methods. Results: We examined records of 131 children in Jigalong and 128 children in Mugarinya. After the pools had been installed, clinic attendance rates for skin infections declined by 68% in Jigalong and by up to 77% in Mugarinya. In Jigalong (where the pre-pool prevalence of infections was higher than in Mugarinya), rates of antibiotic prescription declined by 45%, as did clinic attendance for middle-ear infections (61% reduction) and respiratory tract infections (52% reduction). Conclusion: Swimming pools in remote communities are associated with reduced prevalence of skin infections. Where disease prevalence is high, pools are also associated with reduced rates of antibiotic prescriptions and middle-ear and respiratory tract infections. In communities with resident health staff, examination of clinic records is an efficient method of monitoring the effects of public health interventions on the burden of infectious diseases.